Desarrollo de un módulo de abastecimiento para la fritura de plátano en la empresa “El Campeón” del cantón Chone. - Álava Bravo, Andrea Belén (2016)
The industrial fryer used by “El Campeón” Company, was built empirically, due to the entrepreneurship of the owner. This machine submit drawbacks in both mechanical and electronic. One of these is the chips banana slicer and the product supply, having 40 % of waste, implying a big production losses. Considering this problem the design was performed, construction and commissioning of a supply module for fried bananas, controlling the speed of the cutting blade and automating the product supply, this help to reduce the waste and increase the production. The company has different kinds of frying, like green banana, banana that change color as they mature and mature banana, the slice speed has to be different. This is performed with a frequency variator to controlling the engine blade. For automating the supply product was used an electro pneumatic system, it was designed and build the shapes for the cut, both longitudinal and transversal, coupled to pneumatic actuator. The part of control was performed by the programmable rele LOGO, this reduce the size of the control board and improve the time of production. Was designed and inducted the installation of the power elements and control, in the board, offering up the right protection to the instruments used in the development of this project. With the implementation of this module it was improved to 63,05% of waste, this result will depend on the volume of production and product processing for the factory.